2020
DOI: 10.1186/s12883-020-01945-4
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging and dynamic X-ray’s correlations with dynamic electrophysiological findings in cervical spondylotic myelopathy: a retrospective cohort study

Abstract: Background Dynamic somatosensory evoked potentials (DSSEP) can be used to disclose abnormalities of ascending sensory pathways at dynamic positions and diagnose cervical spondylotic myelopathy (CSM). However, radiographic tests including magnetic resonance imaging (MRI) and dynamic X-ray are used much more widely in the management of CSM. Our study aims to clarify the correlations between several radiographic parameters and the DSSEP results, and further determine their reliability with clinica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 43 publications
1
29
0
Order By: Relevance
“…[3] Somatosensory evoked potential (SSEP) is an objective neurophysiological test widely used in evaluating neurological functions and predicting prognosis in CSM. [4] In our previous studies [5,6], we found most patients had dynamic SSEP (DSSEP) deteriorated upon extension and exion, as other studies suggested [7]. For those patients, their DSSEP N13 amplitude ratios correlated with preoperative mJOA scores and postoperative recovery rates, as well as compressive degrees of the spinal cord in axial MRI and cervical segmental instability in dynamic X-ray.…”
Section: Introductionmentioning
confidence: 72%
See 4 more Smart Citations
“…[3] Somatosensory evoked potential (SSEP) is an objective neurophysiological test widely used in evaluating neurological functions and predicting prognosis in CSM. [4] In our previous studies [5,6], we found most patients had dynamic SSEP (DSSEP) deteriorated upon extension and exion, as other studies suggested [7]. For those patients, their DSSEP N13 amplitude ratios correlated with preoperative mJOA scores and postoperative recovery rates, as well as compressive degrees of the spinal cord in axial MRI and cervical segmental instability in dynamic X-ray.…”
Section: Introductionmentioning
confidence: 72%
“…[6] However, there were some CSM patients presented signi cantly improved DSSEP amplitudes and/or latencies during cervical spine exion and/or extension, whose DSSEP N13 amplitude ratios were obviously unmatched with their MRI compression degrees. [5,6] These patients also frequently presented symptomatic alleviations at extension or exion. The reasons why patients presented abnormal DSSEP upon extension and/or exion positions are still not clear.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations